Evaluation of the bond performance in FRP-brick components re-bonded after initial delamination - Ghiassi, Bahman (2015)
The bond behavior between Fiber Reinforced Polymers (FRPs) and masonry substrates has been the subject of many studies during the last years. Recent accelerated aging tests have shown that bond degradation and FRP delamination are likely to occur in FRP-strengthened masonry components under hygrothermal conditions. While an investigation on the possible methods to improve the durability of these systems is necessary, the applicability of different bond repair methods should also be studied. This paper aims at investigating the debonding mechanisms after repairing delaminated FRP-strengthened masonry components. FRP-strengthened brick specimens, after being delaminated, are repaired with two different adhesives: a conventional epoxy resin and a highly flexible polymer. The latter is used as an innovative adhesive in structural applications. The bond behavior in the repaired specimens is investigated by performing single-lap shear bond tests. Digital image correlation (DIC) is used for deeper investigation of the surface deformation and strains development. The effectiveness of the repair methods is discussed and compared with the strengthened specimens.